Alteration of the Fogera Plain flood regime due to Ribb Dam construction, Upper Blue Nile Basin, Ethiopia. (3rd July 2022) - Mulatu, Chalachew A.; Crosato, Alessandra; Langendoen, Eddy J.; Moges, Michael M.; McClain, Michael E.
Abstract : The Fogera Plain, Ethiopia, is affected by recurrent flooding of the Ribb and Gumara Rivers. A large dam on the Ribb River is under construction for irrigation, but also to reduce flooding. We investigated the effects of the dam on the flood regime of the floodplain wetlands using a combination of hydrodynamic and a rainfall-runoff models. The model was calibrated based on inundation maps retrieved from Landsat images. Pre- and post-dam model comparison for 10 years shows that the dam will reduce the flooding extent by 11%, as it only regulates 23.8% of the upstream watershed. The flood extent and duration necessary to maintain ecologically significant water depths (≥ 0.5 m) show no notable changes. The developed hydrologic and hydrodynamic models can be used to analyze other dam operation and climate change scenarios even though there are uncertainties related to terrain resolution and analysis of hydrological data.